Is Transcreation Another Way of Translating? Subtitling Estrella Damm’s Advertising Campaigns into English - Corrius, Montse; Espasa, Eva (Íkala, Revista de Lenguaje y Cultura, 2023)
The current international advertising scenario has led to a new professional profile within advertising translation called transcreator. Transcreation has an explicit call for creativity and semiotic and cultural adaptation. Beer advertising has tried to respond to this call by undergoing significant changes when this product has been internationally marketed in English in global advertising campaigns. For example, Estrella Damm, advertised as “the beer of Barcelona”, has improved its international positioning with its Mediterráneamente campaign, which started in 2009 and has centred on the association of beer with the Mediterranean culture and enjoyment. Since 2019, the campaign has promoted sustainability as “another way of living”. In this article, we examine the English translation strategies used by Estrella Damm’s campaigns between 2009–2021, which are available on the company’s British website and YouTube channel. Specifically, we focus on the following prominent elements: slogans, cultural references, and songs. To do this, we use a descriptive case study methodology, with textual analysis and semi-structured interviews to the creative director and the translators of Estrella Damm commercials. The analysis shows that this campaign uses strategies that are common in advertising translation: internationalisation, envisaged from the start of campaign; dialogue between translators and art directors; some adaptation to the conventions of the target language and culture, and creativity and co-creation. This emphasizes the added value of transcreation in the translation industry.